Effect of Hemodialysis on Nutritional Status in Chronic Renal Failure Patients - Irwan Setiawan; Purbianto Purbianto (Hypertension Prevention and Control Research Center, The Polytechnic of Health of Banten, 2023)
Chronic kidney failure is a condition where there is a decrease in kidney function in maintaining balance in the body, and the process takes place gradually until there is a decrease in function and the kidney cannot return to its original function. Hemodialysis functions to excrete waste products and toxic substances such as urea and creatinine in the body, but hemodialysis carries the risk of causing malnutrition because nutrients such as protein and glucose, as well as water-soluble vitamins, are also filtered during the hemodialysis process. This study aims to determine the relationship between duration of hemodialysis and nutritional status in chronic kidney patients at the Hemodialysis Unit at Tangerang District General Hospital. The design used in this study was an analytic survey with a cross-sectional approach. Sampling used a purposive sampling technique with a total of 58 respondents. The analysis in this study used the chi-square test. The results of the chi-square test obtained a p-value of 0.038 (α=0.05), which means that there is a relationship between the duration of hemodialysis and nutritional status in chronic kidney patients at the Hemodialysis Unit at the Tangerang Regency General Hospital. It is hoped that health service institutions will improve services by documenting BMI to help monitor the nutritional status of patients while undergoing hemodialysis.